Optimalisasi Beaufort Cipher Menggunakan Pembangkit Kunci RC4 Dalam Penyandian SMS - Diana, Mia; Zebua, Taronisokhi (STIKOM Tunas Bangsa Pematangsiantar, 2018)
The key in the cryptography algorithm is a very important role in the process of encryption and decryption. The more random key numbers are used, the more random the ciphers are generated. The RC4 algorithm and the Beaufort cipher are algorithms of cryptographic techniques. The RC4 algorithm has advantages in generating random keys, whereas Beaufort ciphers have a disadvantage in terms of the number of keys used too much. This research describes how to optimize key formation in Beaufort algorithm by utilizing the key generation process on the RC4 algorithm which is implemented on encoding SMS which until now has not been point-to-point (not directly sent to destination). The results of this study provide convenience for users in the process of generating encryption and decryption keys and generate SMS cipher more random and difficult to understand by others.